The development of a typology of abusive coaching behaviours within youth sport - Raakman, E.; Dorsch, K.; Rhind, D. (International Journal of Sports Science and Coaching, 2011)
The purpose of this article was to create the Typology of Coaching Transgressions model (TOCT), which is concerned with abuse, neglect and violence in youth sport. Comments provided by the Justplay Behaviour Management Program from two competitive hockey associations and one large soccer association were analyzed and sorted to assess the utility of the model to capture inappropriate coaching behaviours. A total of 540 comments were examined deductively using the TOCT. Approximately 80% of coaching transgressions were of an indirect nature (i.e., not directed at the athlete specifically), indicating that young athletes are exposed to forms of abuse, neglect, and violence that may create harm in ways not yet fully understood. These findings illuminate the importance of understanding the nature and impact of coaching conduct on youth sport participants.